061 Sleep Hygiene as an Intervention to Lower Blood Pressure. (3rd May 2021) - Vazquez, Michael; Yang, Huan; Dang, Rammy; Haack, Monika; Mullington, Janet
Abstract: Introduction: Insufficient sleep has been shown to increase the risk of a person developing hypertension. Impaired baroreflex sensitivity (BRS) is one of the known underlying mechanisms involved that is responsible for increasing blood pressure (BP). This project investigates the relationship between sleep, BRS, and BP during Valsalva's Maneuver (VM). Methods: Fifty participants (59.8 ± 1.5 years; 31 women) completed 3 overnight in-hospital stays. The first stay (S1) was a baseline control; the second stay (S2) followed a 4-week wait-list control condition; the third stay (S3) followed an 8-week randomly assigned intervention that used sleep hygiene approaches and scheduling to either A) stabilize sleep timing, or B) stabilize and extend the bed period. The study is still ongoing, and we are blind to whether participants were randomized to arm A or B of the study. A linear regression model analyzing the R-R Interval (RRI) and corresponding systolic BP was used to calculate the BRS function and the maximum change in SBP (BPMax) during Early Phase II (EPII) of VM. Results: There was an increasing BRS trend across the three stays during EPII (p=.051). There was no significant increase between S1 and S2 (p=.876), but BRS significantly increased following 8 weeks of intervention at S3 compared to S1 (p=0.033) and S2 (p=0.037). There was also a significant decrease in BPMax across the three stays during EPII (p<.001). There was no significant decrease in EPII BPMax between S1 and S2 (p=.325), but BPMax significantly decreased in S3 compared to S1 (p<0.001) and S2 (p=0.002). Conclusion: While we are still blind to condition, both conditions are considered active as they both involve stabilizing the sleep period using sleep hygiene. These preliminary data suggest that stabilization of sleep timing and possibly duration, has a positive impact on BP regulation. Support (if any): NIH (R01HL125379 to Dr. Janet Mullington), Harvard Catalyst, Harvard Clinical and Translational Science Center (UL1TR001102).